Direct detection of Tritrichomonas foetus in cattle genital fluid trough loop mediated isothermal amplification of elongation factor 1 alpha 1 - Oyhenart, Jorge (2018)
Testing for Tritrichomonas foetus and exclusion of infected animals is an effective way of improving the reproductive efficiency in a herd. Conventional PCR is inherently more specific than the culture method and quantitative PCR can significantly increase the detection limit. Loop Mediated Isothermal DNA Amplification (LAMP) is gaining interest because the method does not require expensive equipment, specificity and sensitivity can be as high as quantitative PCR. The object of this study was to develop a sensitive and friendly test for point-of-care detection of T. foetus. The LAMP test that targeted T. foetus elongation factor 1 alpha 1 sequences showed high specificity. Sensitivity was 100–1000 times higher than that reached through culture, polymerase chain reaction or with a previously developed LAMP for 5.8 ribosomal sequences. Moreover, T. foetus detection could be performed without DNA purification from infected cervical vaginal mucus (CVM) or smegma samples. The tf-ef1a1 LAMP method was tested for field detection with paper strips soaked in CVM from infected cows and the results were observed 90 min later. Direct detection of T. foetus in CVM with the tf-ef1a1 LAMP showed high sensitivity and specificity, and an overall diagnostic odds ratio of 56 (CI: 13.3–235.0). The tf-ef1a1 LAMP showed great potential for diagnosis and control of T. foetus in resource-challenged regions.